Estimating transfection efficiency in differentiated and undifferentiated neural cells - Alabdullah, Abeer A. (BMC Res Notes, 2019)
OBJECTIVE: Delivery of constructs for silencing or over-expressing genes or their modified versions is a crucial step for studying neuronal cell biology. Therefore, efficient transfection is important for the success of these experimental techniques especially in post-mitotic cells like neurons. In this study, we have assessed the transfection rate, using a previously established protocol, in both primary cortical cultures and neuroblastoma cell lines. Transfection efficiencies in these preparations have not been systematically determined before. RESULTS: Transfection efficiencies obtained herein were (10–12%) for neuroblastoma, (5–12%) for primary astrocytes and (1.3–6%) for primary neurons. We also report on cell-type specific transfection efficiency of neurons and astrocytes within primary cortical cultures when applying cell-type selective transfection protocols. Previous estimations described in primary cortical or hippocampal cultures were either based on general observations or on data derived from unspecified number of biological and/or technical replicates. Also to the best of our knowledge, transfection efficiency of pure primary neuronal cultures or astrocytes cultured in the context of pure or mixed (neurons/astrocytes) population cultures have not been previously determined. The transfection strategy used herein represents a convenient, and a straightforward tool for targeted cell transfection that can be utilized in a variety of in vitro applications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-019-4249-5) contains supplementary material, which is available to authorized users.